A dimer path for CO dissociation on PtSn. Issue 3 (11th January 2019) - Vandichel, Matthias; Grönbeck, Henrik
Abstract : Density functional theory calculations are used to investigate CO adsorption, dissociation and SnO X formation on Pt3 Sn. Abstract : Density functional theory calculations are used to investigate CO adsorption, dissociation and SnO X formation on Pt3 Sn. We find that direct CO dissociation is prevented by high activation energies. An energetically feasible path is instead CO dimer formation followed by C–O bond cleavage. Dimers are formed in the presence of Sn adatoms which effectively stabilize anionic OCCO − species. The presence of Sn adatoms is crucial as dimers are unstable on Pt-only systems. The proposed mechanism may explain recent experimental observations of SnO X and C–C formation as Pt x Sn is exposed to CO.